The Relationship between the Family Environment and Eating Disorder Symptoms in a Saudi Non-Clinical Sample of Students: A Moderated Mediated Model of Automatic Thoughts and Gender - Badra Hamdi Alghanami; Mogeda El Sayed El Keshky (Behavioral Sciences, 2023)
Eating disorders are a global burden and present personal, family, and societal costs. Most evidence in the literature is based on the relationship between a poor family environment and eating disorders, and the evidence of gender interaction in eating disorders is inconsistent. This study aimed to investigate the relationship between family environment and eating disorder symptoms, the mediating role of negative automatic thoughts, and the moderating role of gender using a non-clinical sample of students. A sample of 440 (70.9% females, aged 18–21) participated in this study. They completed the Eating Attitudes Test (EAT-26), the Automatic Thoughts Questionnaire (ATQ negative), and the Brief Family Relationship Scale (BFRS). PROCESS MACRO was used to study these relationships. The main findings revealed that family environment was negatively associated with eating disorder symptoms and that this relationship was mediated by automatic thoughts. Moreover, gender moderated those relationships, and more intensely in females. The results of this study indicate that the prevention of eating disorders should be directed at training individuals to challenge negative thoughts and encourage healthy individuals to be gender mindful.